PENGARUH NET WORKING CAPITAL, LEVERAGE, GROWTH OPPORTUNITY, DAN PROFITABILITY TERHADAP CASH HOLDING - Verent Permata Sari, Rini Tri Hastuti (Jurnal Paradigma Akuntansi, 2020)
The purpose of this empirical research is to examine the influence ofnet working capital, leverage, growth opportunity and profitability toward cash holding. This research uses 125 sample manufactured company listed on the Indonesia Stock Exchange period of 2016-2018. Sample was selected by using purposive sampling method. Data processing techniques in this research using software Eviews 10. The results of this research indicate that all independent variables simultaneously have a significant effect oncash holding. The partially test indicate that net working capital, leverage, and profitability have a significant effect on cash holding, while growth opportunnity have a not significant effect on cash holding.